An overview of modelling approaches and potential solution towards an endgame of tobacco - Abdul Halim, Tisya Farida; Sapiri, Hasimah; Zainal Abidin, Norhaslinda (2015)
A high number of premature mortality due to tobacco use has increased worldwide.Despite control policies being implemented to reduce premature mortality, the rate of smoking prevalence is still high.Moreover, tobacco issues become increasingly difficult since many aspects need to be considered simultaneously.Thus, the purpose of this paper is to present an overview of existing modelling studies on tobacco control system.The background section describes the tobacco issues and its current trends.These models have been categorized according to their modelling approaches either individual or integrated approaches.Next, a framework of modelling approaches based on the integration of multi-criteria decision making, system dynamics and nonlinear programming is proposed, expected to reduce the smoking prevalence. This framework provides guideline for modelling the interaction between smoking behavior and its impacts, tobacco control policies and the effectiveness of each strategy in healthcare.